Postcapitalism, basic income and the end of work: A critique and alternative - Frederick Harry Pitts; Ana C. Dinerstein (University of Bath, Centre for Development Studies (CDS), 2017)
This paper critiques popular academic understandings of development towards a post-capitalist, post-work society based around the automation of production and the provision of a basic income to those displaced by its effects. By focusing on work and its escape as the central issue at stake in the transition to a postcapitalist society, these accounts miss how, at one end, capitalist work is preconditioned by a historically-specific set of antagonistic social relations of constrained social reproduction, and, at the other, by the specific social forms assumed by the results of that work in commodity exchange and the constituted form of the nation-state. Retaining money, commodities and the rule of value under the auspices of a national state postcapitalist and post-work vistas represent abstract 'bad utopias' that break insufficiently with the present, and in some ways make it worse, replacing a wage over which workers can lawfully struggle with a state-administered monetary payment that creates a direct relationship of power between citizen and state. This is highlighted in the potential adoption of basic income as part of authoritarian nationalist policy platforms including that of Nerendra Modi in India. Suggesting that struggles over the contradictory forms assumed by social reproduction in capitalist society are themselves labour struggles and not external to them, we pose a 'concrete utopian' alternative that creates the capacity to reshape the relationship between individuals, society and the rule of money, value and the state rather than reinforce it. To illustrate this we examine the Unemployed Workers Organisations instituted in Argentina. This poses one potential means of devolving monetary and non-monetary resources and power rather than centralising them in the hands of an all-powerful 'postcapitalist' state that would carry all the scars of the society it sets out to surpass. Such a 'concrete utopia' would create space for, and not liquidate or falsely resolve, class struggle in, against and beyond capitalist development.
Keywords: 330